Students Competence in using Present Continuous Tense by the Second Grade Students at SMA Negeri 6 Ternate - Sri Ayu Budi Lestari; Yetty Yetty; Saiful Latif; Taib Latif (Universitas Khairun, 2023)
This research aims to find out the students competence in using present continuous tense by the second grade at SMA Negeri 6 Kota Ternate. This research applied a descriptive quantitative method. The population was the eleventh grade of SMA Negeri 6 Kota Ternate with 47 students. The research sample consisted of 20 students. The data collection was through a writing test and interview. Then, the data were analyzed by descriptive statistical analysis. The results of this study showed that the proportion (frequency and percentage) of the test result was 15% got good, 25% got fairly good, 20% got fair, 5% got poor, and 35% got very poor. Most of the respondents got poor classification. It means that the score of students in present continuous tense is still low. The biggest error that is produced by eleventh grade students of SMA Negeri 6 Kota Ternate in using present continuous tense is because of misformation.